Does Monetary Policy Respond to Macroeconomic Shocks? Evidence from Indonesia - Arintoko, Arintoko; Kadarwati, Nunik (Jurnal Ekonomi & Studi Pembangunan, 2022)
The activist policy is believed by policymakers and economists that monetary policy can respond to macroeconomic shocks to stabilize the economy. This study aims to find evidence and discuss the response of monetary policy to macroeconomic shocks. For this reason, the effects of GDP shocks, inflation shocks, and exchange rate shocks on policy interest rates in the implementation of monetary policy are discussed through vector error correction model (VECM) analysis along with policy interest rate responses involving the long-run relationships. The study period 2001Q1 – 2020Q1 is used as the policy implementation period using the policy interest rate. The results of the analysis show that based on the magnitude of the impact and its contribution, inflation shock and exchange rate shock are the most important macroeconomic variable shocks in influencing the monetary policy stance in Indonesia. Inflation shocks and exchange rate shocks need to be a priority focus for monetary policymakers in an economic environment where uncertainty is increasing and rapidly changing. In addition to the interests of the domestic economy, monetary policy also needs to remain focused on considering and adapting to increasingly dynamic global economic and financial developments.